CITY OF LONDON: THE SECRETS OF STABILITY - M. K. Belyaev (Модернизация, инновация, развитие)
Reasons why the City, oldest London global financial centre, keeps to hold up leading positions in the financial world, are thoroughly discussed. Initially, this phenomenon was explained by dominating position England held as world industrial power. However, the City has not lost its leadership over last decades when England economics suffered bad times. This is explained by traditions, by the history as well as by specific position London holds as place where «business is made» as well as by the trend to «clustering» i.e. concentration characteristic for the market of financial services, all this making it possible for financial companies to cut their costs and to provide their clients with services on more attractive conditions.